Beholden: The Emotional Effects of Having Eye Contact While Breaking Social Norms - Singh, Ranjit Konrad; Voggeser, Birgit Johanna; Göritz, Anja Simone (Frontiers in Psychology, 2021)
This study looks into the role that eye contact plays in helping people to control themselves in social settings and to avoid breaking social norms. Based on previous research it is likely that eye contact increases prosocial behavior via heightened self-awareness and increased interpersonal synchrony. In our study, we propose that eye contact can also support constructive social behavior by causing people to experience heightened embarrassment when they are breaking social norms. We tested this in a lab experiment (N = 60) in which participants read insults at the experimenter (i.e., they exhibited norm breaking behavior). In the experimental condition, participants maintained eye contact with the experimenter. In the control condition, the experimenter did not maintain eye contact. We measured embarrassment with a self-report measure, heart rate to capture arousal, and two observational indicators of embarrassment (hesitation and laughter). In line with our hypotheses, having eye contact during norm breaking behavior as compared to no eye contact led to a stronger increase in self-reported embarrassment, a higher heart rate as well as more hesitation and more laughter. We conclude that eye contact does indeed lead to more embarrassment while breaking social norms. This implies that eye contact gives people the power to punish norm breaking in others by inducing an aversive emotional experience.